The Impact of the Word Webbing Technique on EFL Students’ Descriptive Writing Skills - Ismayanti, Nita; Shofiyuddin, Muh (Jurnal Pendidikan Progresif, 2025)
The Impact of the Word Webbing Technique on EFL Students’ Descriptive Writing Skills. Writing is among the most demanding skills for English as a Foreign Language (EFL) learners because it requires the integration of vocabulary mastery, grammatical accuracy, idea organization, and developing the idea. Many students struggle to put their thoughts into an organized, written form.  This study examined the efficacy of the Word Webbing Technique (WWT) in tackling these obstacles, especially in the composition of descriptive texts.   Objective: This study aimed to evaluate the effectiveness of the word webbing approach in improving the writing skills of tenth-grade students at an Islamic senior high school. Methods: The study employed a quantitative methodology, utilizing a quasi-experimental design with pre-test and post-test non-equivalent groups.  There were thirty-five grade ten students in this study: 18 students from the social class, forming the control group, and 17 students from the science class, forming the experimental group. This research employed pre-tests and post-tests to assess students' writing skills, and then utilized SPSS to analyze the data using an independent sample t-test.  Findings:  The experimental group had an average score of 87.06, whereas the control group had an average score of 71.67.  The experimental group's scores increased from 61.47 to 87.06, whereas the control group's scores rose from 60.83 to 71.67.  The t-test yielded a t-value of 9.227 at a 0.05 significance level (df = 33). These results indicate that WWT can significantly enhance students' writing abilities by facilitating the generation of more ideas, the use of new vocabulary, the application of correct grammar, and the production of more structured and descriptive material.   Conclusion: The WWT is a highly effective writing method for tenth-grade students learning English as a foreign language, enabling them to enhance their descriptive writing skills.  Teachers should utilize this method in the classroom to engage students, encourage them to generate new ideas, and enhance their writing skills. Keywords: word webbing technique (WWT), learning technique, writing skill, descriptive text, EFL writing.